EVALUATING THE EFFECTIVENESS OF DIRECTIONAL RADIATION INTERDIGITAL TRANSDUCER ON INHOMOGENEOUSLY POLARIZED ACOUSTIC LINE - V. G. Basov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
With application of connected waves theory the evaluation of directed radiation efficiency of interdigital executed by inhomogeneous polarization piezosoundlead transducer exciting acoustic sources with a phase shift 90 degrees has obtained.